Corrosion fatigue crack propagation behavior of S135 high–strength drill pipe steel in H2S environment. (March 2019) - Liu, Ming; Luo, Sheji; Shen, Yi; lin, Xiuzhou
Abstract: Corrosion fatigue crack propagation (CFCP) tests were employed to investigate the behavior of S135 low carbon high−strength drill pipe steel under different strain rates in a simulated H2 S containing drilling environment. Results revealed that the CFCP rate curve of the S135 steel has the characteristics of stress corrosion and corrosion fatigue (CF), which can be divided into near threshold, platform and rapid propagation zone. H2 S has an obvious acceleration effect on the CFCP rate of S135 steel, the propagation rate of S135 steel in H2 S solution is about 10 times more than that of in air. The stress ratio R has different effects on rapid propagation and near threshold zone. In the rapid propagation zone, the order of CFCP rate from high to low is R = 0.1 > R = 0.3 > R = 0.5, while the order of near threshold zone just shows the opposite. In the near threshold zone, the CFCP rate increases with the increasing of the stress ratio R . Based on the proposed Corrosion–Passivation–Fracture model and elastic fracture mechanics, the CFCP rate expression of S135 steel in H2 S solution is d a d N cf = 1.927 × 10 ‐ 9 Δ K − 6.15 1 − R 0.59 2, which can be used to predict the CFCP life in practical engineering. Fracture analysis results shows that the CFCP of S135 steel in H2 S solution is mainly controlled by anodic dissolution and hydrogen embrittlement. Highlights: Corrosion fatigue crack propagation (CFCP) tests were employed. S135 steel has the characteristics of stress corrosion and corrosion fatigue in H2 S solution. The stress ratio R has different effects on rapid propagation and near threshold zone. CFCP of S135 steel is controlled by anodic dissolution and hydrogen embrittlement.